Arqueologia e conformação de identidades das comunidades indígenas do Nordeste: um estudo de caso dos Xucuru-Kariri - Pinto, Karina Lima de Miranda (2013)
The category "Indians of the Northeast," widely studied in anthropology since the late 1940s, has as its main concern the process of ethnic reclaiming and restructuring of indigenous peoples in this region. This category - classified by the "non-Indian world" includes the Xucuru-Kariri of Palmeira dos Índios / AL, who since the 1950s have been gaining ground in the fight for recognition and free exercise of their ethnic identity. In order to affirm their identity, the Xucuru-Kariri have attributed symbolic value to the city‟s pre-colonial archaeological sites, which correspond to their ancestry in the region. Thus, throughout the process of group restructuring, the sites have always been present in works produced by anthropologists, historians, and archaeologists. However, during their archaeological production, the sites were classified according to a cultural-historical perspective which, within academia, removed the possibility of a dialogue between the Xucuru-Kariri and the researchers. This paper, guided by a public archaeological bias, as well as theoretical and methodological multivocal precepts, examines the place that material culture and archaeology occupies for the Xucuru-Kariri, as well as what this field has done for them. I conducted a participatory mapping that promoted a horizontal dialogue between me as a researcher, and the community; and through the current perspective of reflexive archaeology, I attempted to break the hegemonic view that often results in epistemic violence as determined by modernity in regards to the dichotomous processes among different societies. The results obtained carry the vision of local materiality from the perspective of the Xucuru-Kariri, how it is manipulated by the group, and how it is signified within their cosmological universe and (re)signified in the "non-Indian world.